The 1549 rebellions and the making of early modern England - Wood, Andy (Cambridge University, 2013)
This is a major new study of the1549 rebellions, the largest and most important risings in Tudor England. Based upon extensive new archival evidence, the book sheds fresh light on the causes, course and long-term consequences of the insurrections. Andy Wood focuses on key themes in the new social history of politics, concerning the end of medieval popular rebellion; the Reformation and popular politics; popular political language; early modern state formation; speech, silence and social relations; and social memory and the historical representation of the rebellions. He examines the long-term significance of the rebellions for the development of English society, arguing that they represent an important moment of discontinuity between the late medieval and the early modern periods. This compelling new history of Tudor politics from the bottom up will be essential reading for late medieval and early modern historians as well as early modern literary critics. Andy Wood is Professor of Social History at the School of History, University of East Anglia.